Biodegradation Kinetics of Free Cyanide in Fusarium oxysporum-Beta vulgaris Waste-metal (As, Cu, Fe, Pb, Zn) Cultures under Alkaline Conditions - Enoch A. Akinpelu; Seteno Karabo Ntwampe; Ncumisa Mpongwana; Felix Nchu; Tunde V. Ojumu (BioResources, 2016)
The kinetics of free cyanide biodegradation were investigated under simulated winter (5 °C) and optimum conditions (22 °C and pH of 11) using a Fusarium oxysporum isolate grown on Beta vulgaris waste as a sole carbon source in the presence of heavy metals, i.e. As, Fe, Cu, Pb, and Zn. The highest free cyanide degradation efficiency was 77% and 51% at 22 °C and 5 °C respectively, in cultures containing free cyanide concentration of 100 mg F-CN/L. When compared with the simulated winter conditions (5 °C), the specific population growth rate increased 4-fold, 5-fold, and 6-fold in 100, 200 and 300 mg F-CN/L, respectively, for cultures incubated at 22 °C in comparison to cultures at 5 °C; an indication that the Fusarium oxysporum cyanide degrading isolate prefers a higher temperature for growth and cyanide biodegradation purposes. The estimated energy of activation for cellular respiration during cyanide degradation was 44.9, 54, and 63.5 kJ/mol for 100, 200, and 300 mg F-CN/L cultures, respectively, for the change in temperature from 5 to 22 °C.